Temporary evacuation and relief centre design management in Malaysia: an overview / Ruwaidy Mat Rasul and Muhammad Muizzuddin Darus - Mat Rasul, Ruwaidy; Darus, Muhammad Muizzuddin (2016)
The study mainly focuses on natural disaster temporary evacuation and relief centre design management which highlights on the monsoon floods in Malaysia as a case study. Currently, the type of evacuation centre that has been practiced is often referred to government or public facilities, such as mosques, schools, churches or even community halls. The after affect of every event is devastating which leaves the building in a state of destructions of property, garbage and sewerage system is clogged. On the other hand, the location wise is far most important in order to cater for accessibility of victims and rescuing team. Using interviews and observations as data collection methods, it is assured that the natural disaster situation of temporary evacuation system requires improvements in order to facilitate the victims, rescuers or to salvage public property. Nevertheless, Non-Governmental Organizations always provide temporary tents or shelters, of which that only focuses on some part of the needs; the resting place. This is however is not enough considering the situations of the victims from various family sizes and ages such as toddlers and senior citizens. Apart from foods and warm resting shelter, medication is a priority in order to accommodate the needy; physically and emotionally. With that, the inflatable type of shelter which is portable and easy to assemble and install is recommended. As a result, it leads towards the design management which needed to be considered such as; safe zone area, shelter management, hygienic system and accessibility for land or/and air transportation. The ‘togetherness’ concept under one roof makes a situation more manageable especially in such difficult and stressful time. Thus, a few recommendation plans with a conceptual size of required area has been suggested. All these plans have similar temporary evacuation and relief centre management system with different plan arrangements. Moreover, these portable temporary shelters can be kept at any local Fire and Rescue Department or any District Police Station as it would be logistically more convenient. Most of the victims hope that the temporary evacuation centre will provide them good facilities and basic comfort. Being emotionally affected, they also need a proper medication and attention. Natural disasters never discriminate any gender or ages as it will cause suffers and tortures who ever that may be involved.